2013
DOI: 10.1172/jci70422
|View full text |Cite
|
Sign up to set email alerts
|

Platelets mediate lymphovenous hemostasis to maintain blood-lymphatic separation throughout life

Abstract: Mammals transport blood through a high-pressure, closed vascular network and lymph through a lowpressure, open vascular network. These vascular networks connect at the lymphovenous (LV) junction, where lymph drains into blood and an LV valve (LVV) prevents backflow of blood into lymphatic vessels. Here we describe an essential role for platelets in preventing blood from entering the lymphatic system at the LV junction. Loss of CLEC2, a receptor that activates platelets in response to lymphatic endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
217
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(231 citation statements)
references
References 39 publications
10
217
0
1
Order By: Relevance
“…This phenomenon validates a remarkable increase in our understanding regarding the roles of platelets in haemostasis, thrombosis and wound repair (13). Correspondingly, current evidence has shown that platelets are entangled in many other physiological and pathological processes beyond haemostasis and thrombosis such immuno-thrombosis, the development of atherosclerosis, lymphatic vessel enlargement, angiogenesis and tumour metastasis (14)(15)(16).…”
Section: Development and Platelet Formationsupporting
confidence: 61%
“…This phenomenon validates a remarkable increase in our understanding regarding the roles of platelets in haemostasis, thrombosis and wound repair (13). Correspondingly, current evidence has shown that platelets are entangled in many other physiological and pathological processes beyond haemostasis and thrombosis such immuno-thrombosis, the development of atherosclerosis, lymphatic vessel enlargement, angiogenesis and tumour metastasis (14)(15)(16).…”
Section: Development and Platelet Formationsupporting
confidence: 61%
“…Collecting vessels are composed of contractile lymphangions that propel lymph in a unidirectional manner, with the help of intraluminal bi‐leaflet valves, as well as smooth muscle cells. Eventually, lymph passes through the lymphovenous junction and reaches the blood circulation via the subclavian vein 5. Junctional organization of LECs in initial lymphatics and collecting vessels is crucial to vessel integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, platelets regulate the blood/lymphatic vessel separation by inhibiting the proliferation, migration, and tube formation of LECs, upon the interaction of C‐type lectin‐like receptor 2 (CLEC‐2) with podoplanin 8. Platelet activity has also been shown to be required throughout life in order to maintain the lymphovenous junction integrity 5. In addition to the hemostatic role of platelets in maintaining lymphatic5 and blood vessel integrity,9 platelets have been shown to act through their secreted active releasates and platelet microparticles, also called extracellular vesicles (EVs), to promote inflammation10, 11, 12 and conversely, to secure inflamed vessels 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our further studies focused on analysis of the lymphatic valve phenotype. We analysed whether the role of Cdk5 in lymphatic valve formation also encompasses lymphovenous valves, which separate the primordial thoracic duct (pTD) and adjacent cardinal vein (CV) 3,4,25,26 . Three-dimensional reconstructions of image stacks obtained by optical sectioning of entire whole-mount immunostained E12.5 embryos showed lymphovenous valves, that is, two contact sites of double layer of endothelial cells with high Prox1 expression, in control littermates and demonstrated frequent failure of lymphovenous valve formation in Cdk5 fl/fl Tie2Cre embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%